Análisis energético de un sistema de gasificación de biomasa para la producción de gas de síntesis (2018)
In the present work, the mass and energy balance of a technological scheme is analyzed to analyze and evaluate the gasification process. A computational tool is developed, studying the variables and parameters that influence the gasification process to obtain synthesis gas. To carry out this objective, it is necessary to carry out the characterization of the biomass that is going to be subjected to the decomposition and transformation process; Within the characterization is the next analysis, elemental analysis and calorific power. In the project, three types of raw material are studied, such as coffee husk, wood and rubber. The gasification process can be divided into several stages. The first stage corresponds to drying, which is the pre-treatment that is done to the biomass for subsequent processes. The next stage is the pyrolysis process, here the biomass decomposes to form gaseous, liquid and solid products, in addition, it is necessary to know the reaction kinetics for each of the components of the biomass. Once these products are formed, the carbonized ones undergo the gasification process, having contact with a reaction agent, in this case water, to convert these solid products into gas.